The second mountain : the quest for a moral life - Brooks, David, 1961- (New York : Random House, 2019)
Conservative columnist David Brooks explores the four commitments that define a life of meaning and purpose: to a spouse and family, to a vocation, to a philosophy or faith, and to a community. Our personal fulfillment depends on how well we choose and execute these commitments. Brooks looks at a range of people who have lived joyous, committed lives, and who have embraced the necessity and beauty of dependence. He gathers their wisdom on how to choose a partner, how to pick a vocation, how to live out a philosophy, and how we can begin to integrate our commitments into one overriding purpose.
"Every so often, you meet people who radiate joy--who seem to know why they were put on this earth, who glow with a kind of inner light. Life, for these people, has often followed what we might think of as a two-mountain shape. They get out of school, they start a career, and they begin climbing the mountain they thought they were meant to climb. Their goals on this first mountain are the ones our culture endorses: to be a success, to make your mark, to experience personal happiness. But when they get to the top of that mountain, something happens. They look around and find the view ... unsatisfying. They realize: This wasn't my mountain after all. There's another, bigger mountain out there that is actually my mountain. And so they embark on a new journey. On the second mountain, life moves from self-centered to other-centered. They want the things that are truly worth wanting, not the things other people tell them to want. They embrace a life of interdependence, not independence. They surrender to a life of commitment. In [this book], David Brooks explores the four commitments that define a life of meaning and purpose: to a spouse and family, to a vocation, to a philosophy or faith, and to a community. Our personal fulfillment depends on how well we choose and execute these commitments. Brooks looks at a range of people who have lived joyous, committed lives, and who have embraced the necessity and beauty of dependence. He gathers their wisdom on how to choose a partner, how to pick a vocation, how to live out a philosophy, and how we can begin to integrate our commitments into one overriding purpose. In short, this book is meant to help us all lead more meaningful lives. But it's also a provocative social commentary. We live in a society, Brooks argues, that celebrates freedom, that tells us to be true to ourselves, at the expense of surrendering to a cause, rooting ourselves in a neighborhood, binding ourselves to others by social solidarity and love. We have taken individualism to the extreme--and in the process we have torn the social fabric in a thousand different ways. The path to repair is through making deeper commitments. In The Second Mountain, Brooks shows what can happen when we put commitment-making at the center of our lives. "--Dust jacket.
PART I: THE TWO MOUNTAINS. Moral ecologies ; The Instagram life ; The insecure overachiever ; The valley ; The wilderness ; Heart and soul ; The committed life ; The second mountain -- THE FOUR COMMITMENTS. PART II: VOCATION. What vocation looks like ; The annunciation moment ; What mentors do ; Vampire problems ; Mastery -- PART III: MARRIAGE. The maximum marriage ; The stages of intimacy ; The marriage decision ; Marriage: the school you build together -- PART IV. PHILOSOPHY AND FAITH. Intellectual commitments ; Religious commitment ; A most unexpected turn of events ; Ramps and walls ; PART V: COMMUNITY. The stages of community building -- Conclusion: The Relationalist Manifesto.
Includes bibliographical references (pages 317-327) and index.
6 10 31
Keywords: Social interaction; Caring; Conduct of life; Relationism; Conduct of life; Relationism; Social interaction